2006
DOI: 10.1111/j.1466-8238.2006.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Imprints of glacial refugia in the modern genetic diversity of Pinus sylvestris

Abstract: Aim To understand the impact of glacial refugia and migration pathways on the modern genetic diversity of Pinus sylvestris . LocationThe study was carried out throughout Europe.Methods An extended set of data of pollen and macrofossil remains was used to locate the glacial refugia and reconstruct the migrating routes of P. sylvestris throughout Europe. A vegetation model was used to simulate the extent of the potential refugia during the last glacial period. At the same time a genetic survey was carried out on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 47 publications
5
76
1
1
Order By: Relevance
“…For example, Picea abies can tolerate frosts up to -38 0 C as long as annual rainfall is at least 400 mm (Ravazzi, 2002), limits that lie well within the modelled glacial climate for southwest England. Similarly, Cheddadi et al, (2006) show that the potential LGM distribution of Pinus sylvestris, determined by applying modern climatic limits of this species to modelled climate reconstructions, extends as far north as Cornwall. Investigations of palaeoecological evidence for the timing and provenance of postglacial tree migration in the British Isles (Birks, 1989) and genetics (Ennos et al, 1997) have both concluded that a glacial refugium for P. sylvestris in north-central Europe is likely.…”
Section: (3) Survival Of Treesmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, Picea abies can tolerate frosts up to -38 0 C as long as annual rainfall is at least 400 mm (Ravazzi, 2002), limits that lie well within the modelled glacial climate for southwest England. Similarly, Cheddadi et al, (2006) show that the potential LGM distribution of Pinus sylvestris, determined by applying modern climatic limits of this species to modelled climate reconstructions, extends as far north as Cornwall. Investigations of palaeoecological evidence for the timing and provenance of postglacial tree migration in the British Isles (Birks, 1989) and genetics (Ennos et al, 1997) have both concluded that a glacial refugium for P. sylvestris in north-central Europe is likely.…”
Section: (3) Survival Of Treesmentioning
confidence: 91%
“…Picea, for example, is most sensitive to extreme continental climate and in particular to winter desiccation (Ravazzi 2002) whilst Abies alba is drought intolerant (Terhune-Berson et al, 2004). Pinus sylvestris can tolerate temperatures as low as -18 o C but does not survive today in areas that experience less than 400 mm annual rainfall (Cheddadi et al, 2006). Moisture dependency may explain the postulated occurrence of these three conifers in the oceanic setting of southwestern England during the LGM.…”
Section: (3) Survival Of Treesmentioning
confidence: 99%
“…At present, P. mugo and P. uncinata form mostly allopatric and discontinuous populations in mountainous regions of Europe, whereas P. uliginosa is restricted to some post-glacial peatbogs in Central Europe. Macrofossil data indicate an early Holocene presence of conifers at high elevations (> 2000 m) in the northwestern Alps and Central Europe (Cheddadi et al, 2006;Blarquez et al, 2010), suggesting that some populations of cold-tolerant species could have survived the last glacial maximum in mountain refugia located north of well-known species hotspots in the Iberian, Apennine or Balkan peninsulas (Petit et al, 2003). For species such as P. mugo and P. uncinata, post-glacial expansion at their lower altitudinal limit was followed, with climate warming, by gradual retreat to higher elevations (Burga, 1988;Ramil-Rego et al, 1998, Benito Garzón, Sánchez de Dios & Sáinz Ollero, 2007.…”
Section: Demographic Patterns Of Nucleotide Variationmentioning
confidence: 99%
“…The currently observed genetic inter-population variability of Scots pine is due to its extensive Euro-Siberian range, its distinct geographic populations from various glacial refuges, the micro-evolutionary processes occurring during the migration of its pollen and seeds after the last glaciation, and dominant cross pollination (Critchfield, Little 1966;Rudin, Lindgren 1977;Shen et al 1981;Sinclair et al;1998, Soranzo et al 2000Labra et al 2006;Naydenov et al 2007;Pyhäjärvi et al 2008;Cheddadi et al 2006). Populations of Scots pine in Europe also exhibit characteristic clinical variability associated with, among other things, the initiation of spring growth or the characteristic variations of needles observed in north-south transects (Gier-tych 1993, Urbaniak 1998.…”
Section: Introductionmentioning
confidence: 99%